Aroma composition of 2‐year‐old New Zealand Pinot Noir wine and its relationship to sensory characteristics using canonical correlation analysis and addition/omission tests. (17th June 2015) - Tomasino, E.; Harrison, R.; Breitmeyer, J.; Sedcole, R.; Sherlock, R.; Frost, A.
Abstract Background and Aims Relationships between the chemical composition and the sensory perception of red wines are generally poorly understood. In New Zealand, the vineyard area of Pinot Noir has increased markedly and wines from this red cultivar now constitute a significant proportion of total production. The aim of this study was to identify aroma compounds of major sensory significance in New Zealand Pinot Noir wines. Methods and Results The concentration of 34 aroma chemicals in 32 New Zealand Pinot Noir wines was quantified using three separate solid‐phase microextraction‐GC‐MS methods. Relationships between these chemical data and sensory data obtained from the same wines were investigated with canonical correlation analysis. Subsequently, correlation results were validated with addition/omissions tests. Ethyl octanoate was found to increase red cherry aroma, the combination of ethyl octanoate and ethyl decanoate enhanced black cherry aroma, and 2‐phenyl ethanol increased violet aroma. Benzaldehyde altered Pinot Noir aroma but its effect on specific attributes was unclear. Conclusions The influence of benzaldehyde, ethyl octanoate and 2‐phenyl ethanol on the aroma of Pinot Noir wine was consistent with previous studies conducted on Merlot and Cabernet Sauvignon wines. This indicated that the contribution of these compounds is similar in a range of red wines. Ethyl decanoate appeared to act as an aroma enhancer compound when in combination with ethyl octanoate. Significance of the Study Improved knowledge of key aroma and flavour components and the factors that influence their concentration is required to allow producers to manipulate better sensory characteristics to meet the preferences of specific markets. This study provides new information on important aroma compounds in New Zealand Pinot Noir which can lead to future research on modulating factors.